2014
DOI: 10.1084/jem.20130977
|View full text |Cite|
|
Sign up to set email alerts
|

BRAF-V600E expression in precursor versus differentiated dendritic cells defines clinically distinct LCH risk groups

Abstract: BRAF-V600E expression is identified in hematopoietic progenitor and precursor myeloid dendritic cells in patients with high-risk LCH, and enforced expression of BRAF-V600E in CD11c+ cells recapitulates a high-risk LCH-like phenotype in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
454
6
34

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(517 citation statements)
references
References 39 publications
23
454
6
34
Order By: Relevance
“…Despite its rarity, ECD includes clinically variable disorders that range from asymptomatic bone infiltration to multiorganic diseases and its clinical course is determined by the extent and distribution of the disease [2]. Recently, major genetic and molecular advances including the detection of recurrent BRAF V600E gain-of-function mutations in biopsies and in peripheral blood of ECD patients [6,16], as well as the recognition of BRAF aberrations in early myelomonocytic precursors or in hematopoietic stem cells of patients with Langerhans cell histiocytosis (LCH) [17], have supported the hypothesis that histiocytoses are myeloid neoplasms. CNS involvement has been traditionally considered an adverse prognostic feature in various forms of myeloid malignancies, requiring the use of both preventive and CNSdirected therapy [18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Despite its rarity, ECD includes clinically variable disorders that range from asymptomatic bone infiltration to multiorganic diseases and its clinical course is determined by the extent and distribution of the disease [2]. Recently, major genetic and molecular advances including the detection of recurrent BRAF V600E gain-of-function mutations in biopsies and in peripheral blood of ECD patients [6,16], as well as the recognition of BRAF aberrations in early myelomonocytic precursors or in hematopoietic stem cells of patients with Langerhans cell histiocytosis (LCH) [17], have supported the hypothesis that histiocytoses are myeloid neoplasms. CNS involvement has been traditionally considered an adverse prognostic feature in various forms of myeloid malignancies, requiring the use of both preventive and CNSdirected therapy [18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The scheme illustrating signalling pathways involved in the control of histiocytic cell proliferation is shown in Figure 1. Furthermore, in patients with MS-LCH, it has been demonstrated that mutation of the BRAFV 600E gene occurs in myeloid cells, whereas in patients with SS-LCH, mutations are found solely in cells originating from infiltrates [19].…”
Section: Pathogenesismentioning
confidence: 99%
“…The patients qualified for targeted therapy need to be tested for mutations within the BRAF, ARAS, NRAS, KRAS and MAP2K genes [16][17][18][19]. Moreover, a novel diagnostic technique used in monitoring of treatment with BRAF inhibitors, is the analysis of the BRAF V600E gene mutation in circulating serum DNA [17].…”
Section: Pulmonary Function Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…En effet, quelques mutations touchant d'autres acteurs de cette voie ont également été rapportées, telles que MAP2K1 [25,26]. La démonstration expérimentale du rôle clé de BRAF V600E a été apportée récemment par des modèles murins [27]. L'expression de l'allèle mutant dans les cellules dendritiques langérine + ou leurs précurseurs CD11c + induit un tableau clinico-pathologique proche de la pathologie humaine.…”
Section: Physiopathologieunclassified